Faktor Intrinsik dan Ekstrinsik Dimoderasi Motivasi Kerja Terhadap Kinerja Guru - Leni Amalia Anggraeni (JURNAL MANAJERIAL, 2021)
Background – Competent teachers can produce quality education. The problem that exists is the number of teachers in schools who lack motivation, this is due to the low enthusiasm of teachers when teaching in several schools. In addition, teacher workloads that exceed the limit and lack of training to improve teacher skills also lead to a lack of teacher motivation. The solution is the need to increase work motivation from both extrinsic and intrinsic factors. Purpose – To find out the influence of instristic and extraneous factors moderated work motivation on teacher performance. Design/Methodology/Approach - This research method uses a causality research design. The population of the study was 86 junior high school teachers in Poncokusumo District. With the research sample 46 SMP teachers who have been certified. The approach used is quantitative with Moderated Regression Analysis (MRA). Result and Discussion - The results of data analysis state: (1) intrinsic factors affect teacher performance, (2) extrinsic factors affect teacher performance, and (3) moderated intrinsic and extrinsic factors affect teacher performance. Conclusion – The results of this study are the intrinsic and extrinsic factors which are moderated by motivation have a significant effect on performance. Motivation strengthens the relationship between intrinsic and external factors on teacher performance in junior high schools in Poncokusumo sub-district. Research Implications - This research has implications for the influence of intrinsic and extrinsic factors as well as motivation as moderation on teacher performance